Influence of Steam Curing on the Performance of High-strength Concrete Incorporating Metakaolin - Zeyad, Abdullah M.; Shah, Amirrudin M.; Megat Johari, Megat Azmi; Mutnbak, Mohammed (Periodica Polytechnica Civil Engineering, 2024)
This study aims to investigate the influence of steam curing on the performance of high-strength concrete incorporating metakaolin. An experimental study was conducted to investigate the compressive strength, chloride permeability, initial surface absorption, and water absorption, as well as thermal degradation under various steam curing scenarios. Four concrete mixtures were prepared in this study, each with different percentages of metakaolin, as partial substitution of cement weight of 0%, 5%, 10%, and 15%. The water–binder ratio was set to 0.32 in all mixtures. The specimens underwent steam curing for 0, 4, 8, and 16 hours at a temperature of 55 °C. Results indicate that the specimens that have been steam cured and contained metakaolin exhibit improved compressive strength during the initial stages of their strength development. Steam curing has been demonstrated to enhance the concrete’s resistance to chloride penetration and reduce initial surface absorption while increasing water absorption. The optimal replacement of cement with metakaolin to enhance strength and transport properties in high-strength concrete under steam curing regimes is between 10% and 15%. Future research could examine the effects of long-term steam curing on the durability and performance of concrete incorporating an optimal proportion of metakaolin.